The history of educational measurement : key advancements in theory, policy, and practice - Clauser, Brian E.; Bunch, Michael B. (New York, NY : Routledge, 2022)
"The History of Educational Measurement collects essays on the most important topics in educational testing, measurement, and psychometrics. Authored by the field's top scholars, this book offers unique historical viewpoints, from origins to modern applications, of formal testing programs and mental measurement theories. Topics as varied as large-scale testing, validity, item-response theory, federal involvement, and notable assessment controversies complete a survey of the field's greatest challenges and most important achievements. Graduate students, researchers, industry professionals, and other stakeholders will find this volume relevant for years to come"--
Early efforts / Luz Bay and Terry Ackerman -- Development and evolution of the SAT and ACT / Michelle Croft and Jonathan J. Beard -- The history of norm- and criterion-referenced testing / Kurt F. Geisinger -- The role of the federal government in shaping educational testing policy and practice / Michael B. Bunch -- Historical milestones in the assessment of English learners / Jamal Abedi and Cecilia Sanchez -- Evolving notions of fairness in testing in the United States / Stephen G. Sireci and Jennifer Randall -- A century of testing controversies / Rebecca Zwick -- A history of classical test theory / Brian E. Clauser -- The evolution of the concept of validity / Michael Kane and Brent Bridgeman -- Generalizability theory / Robert L. Brennan -- A history of scaling and its relationship to measurement / Derek C. Briggs -- A history of Bayesian inference in educational measurement / Roy Levy and Robert J. Mislevy -- History of test equating methods and practices through 1985 / Michael J. Kolen -- A history of Rasch measurement theory / George Engelhard, Jr.
Keywords: Educational tests and measurements -- History; EDUCATION / Testing & Measurement; PSYCHOLOGY / Assessment, Testing & Measurement; EDUCATION / History